Factors causing livery flavor in beef steaks from the chuck and loin - E.J. Yancey; Michael E. Dikeman; K.A. Hachmeister; Edgar Chambers IV; George A. Milliken; E. Dressler (Kansas Agricultural Experiment Station Research Reports, 2003)
The infraspinatus muscle (top blade) from the chuck clod, the gluteus medius muscle (top sirloin) from the sirloin, and the psoas major muscle (tenderloin) from the loin were obtained from 140 A- and B-maturity carcasses with either low-Slight or Small marbling and with either normal pH (5.7 or less) or high ultimate pH (6.0 or higher) to evaluate factors that could cause livery flavor in cooked beef. Muscles were aged for 7, 14, 21, or 35 days. A highly trained, flavor-profile sensory panel evaluated charbroiled steaks from these muscles. Approximately 8% of all sensory panelist judgments were scored to have some livery flavor. Numerous statistical interactions were found among traits, which made it difficult to make clear conclusions. In general, marbling and aging time had little direct effect on livery flavor, and livery flavor was not related to raw muscle lipid oxidation.
Keywords: Cattlemen& #x27; s Day; 2003; Kansas Agricultural Experiment Station contribution; no. 03-272-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 908; Beef; Livery flavor; Chuck; Loin